TEACHING ELEMENTARY SCHOOL BY WHOLE BRAIN TEACHING; BETWEEN STRATEGY AND CHARACTER EDUCATION - Ahmad Arinal Haq (Universitas Islam Nahdlatul Ulama Jepara, 2018)
Teaching nowadays as mandated by 2013 national curriculum is brought among pedagogical and affective dimension. Teacher should be aware to both strategy and character education for students. Teaching English for elementary school needs strategies to adopt, in other hand, character education cannot be taught through as one single unit. Whole Brain Teaching (WBT) treats every child to have four brain areas that require close attention. The procedures of WBT cover Class-Yes, Five classroom rules, Teach-Oke, The Scoreboard, Switch, Mirror, Hand and eyes. The study aims to find the character education gained through WBT. To achieve the purpose, descriptive qualitative research method was used in the study with observation and interview to teacher. The data was gained through questionnaire, to measure students’ perception for self-assessment toward character education. Study was conducted at SD 02 Wates, Undaan, Kudus for two meetings of vocabulary class. This study involved 16 students as observed participants. Result of investigation reveals character virtues educated through WBT as politeness, creativity, responsibility, respect and cooperative. Implication of this study is bringing strategy enriched with character education to teach English.